Given the graph of f(x) below, graph g(x) = f(x - 2) - 1 . State the value of g(3)
![Given the graph of fx below graph gx fx 2 1 State the value of g3 class=](https://us-static.z-dn.net/files/d4e/2e54311d69d2be67347a18f182d148d6.png)
Answer:
g(3)=2
Step-by-step explanation:
Use g(x)=f(x-2)-1
the " - 2" inside the parenthesis with the x will shift the whole graph to the right 2 units. (Shown in dashed red on the image) The " - 1 " at the end of the expression will slide the whole graph down one unit (see image shown in purple) The image shown in purple is the final g(x).
to find g(3) (see image in yellow highlight)
g(3)=2